Legal Protection for Gig Economy Workers from the Perspective of Labor Law in Indonesia - Indra; Nawangsari, Sefti Afi (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The gig economy has experienced rapid growth in Indonesia, with a rising number of platform-based workers engaged through digital platforms such as Gojek, Grab, Shopee, and Tokopedia. However, the legal status of gig workers remains unclear, leading to weak labor protections, particularly in terms of access to social security and compliance with minimum wage standards. This study aims to analyze the legal protection available for gig workers in Indonesia and identify regulatory reforms necessary to improve their welfare. Using a normative juridical and empirical approach, the research examines existing labor regulations and conducts a survey involving 300 gig workers in the transportation, logistics, and digital service sectors. The findings reveal that 60% of gig workers lack social security coverage, 70% do not receive wages that meet minimum standards, and only 20% have formal employment contracts. Furthermore, 72% of workers report income instability, while 85% express the need for clearer regulations to safeguard their rights. The study highlights that the ambiguous legal status of gig workers in Indonesia contributes to high job insecurity and significant disparities in labor protection compared to formal sector employees. Therefore, more adaptive regulatory reforms are needed to ensure that gig workers receive legal protection equivalent to that of workers in the formal sector. The findings of this study are expected to serve as a foundation for policymakers in designing more inclusive and responsive labor regulations that address the evolving dynamics of employment in the digital era.